(3GdHfhc GdeQcRjI hGdSjGSGJ GdfbOjI (B/s - (3GdOhjQj, RcQjGs; (3GdSGeQGFj, jSQis ((3YeGf(B: s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B, s, 2006)
(3fTCI hJWhQ GdHfhc GdeQcRjI(B- (3EUOGQ GdfbhO hHfc GdMcheI(B- (3GdHfc GdeQcRj cHfc ddHfhc hcbje Ydi GMJjGWGJ GdYedGJ GdCLfHjI(B- (3EOGQIGdEFJeGf GdeUQaj(B- (3GSJbdGdjI GdHfhc GdeQcRjI(B- (3GdHfhc GdeQcRjI hGdJfejI GdEbJUGOjI(B- (3GdSjGSI GdfbOjI hGdHfhc GdeQcRjI aj GdOhd GdfGejI(B- (3JLGQH GdHfhc GdeQcRjI aj GdYGde(B.s
Keywords: (3GdHfhcs; (3GdfbhOs